Biblioteca virtual como recurso educacional para o ensino de ciências da natureza na UEB Dra. Maria Alice Coutinho São Luís-MA - GONÇALVES, Cristiane Silva (2024)
This research addresses the theme of the virtual library as an educational resource for teaching Natural Sciences and aimed to investigate the use of the physical library by Natural Sciences teachers, with a view to building a virtual library as an educational resource for the Natural Sciences field in the context of UEB Dra. Maria Alice Coutinho in São Luís-MA. The chosen approach was qualitative, and the selected method was a case study. The research participants were two teachers from the school who teach the Natural Sciences subject and two librarians from SEMED, in the municipality of São Luís-MA. Semi-structured interviews were used as data collection instruments. The interviews were conducted in person. The research data were analyzed from the perspective of Bardin's Content Analysis (2016). The findings revealed that some teachers make little use of the library space for activities and that there is a lack of specific teaching materials for the subject. It was noted that teachers used WhatsApp, demonstrative videos of experiments, and videos available on YouTube, as well as the use of Kahoot to engage students. However, the identified limitation was the quality of the internet connection, which restricted the effective use of these technologies. The research also revealed that only three librarians are responsible for serving all the schools in the municipal network, and the collection in school libraries is guaranteed through the maintenance and acquisition cycle of materials by the National Book and Teaching Material Program (PNLD). The presence of teachers from various subjects, including Natural Sciences, and students in the libraries was noted, with collaboration between teachers and librarians occurring whenever possible. It was also discovered that there are 256 Basic Education establishments in the municipal network, with 96 schools being Elementary Schools with school libraries and, at the time of the research, the network had 127 reading environments, of which only 30 had been included in the Giroteca project, which includes a physical and digital collection, as well as technological equipment such as laptops and printers. The research revealed that there are no virtual libraries in the municipal schools to date. Thus, there emerges a need for investments in infrastructure, human, material, and technological resources, professional training, and teaching resources, aiming to improve the teaching of Natural Sciences and the use of libraries in the municipal schools of São Luís. The participation of teachers and librarians was fundamental for the construction of the virtual library created using the Canva platform. The educational resource can contribute to the dynamism of classes and activities developed by teachers, enhancing the teaching and learning of this area of knowledge and aiding in the scientific and citizen critical formation.